Electricity Generation from Slabs of Construction and Demolition Waste and Waste Electrical and Electronic Equipment - Carlos A. Castaneda-Olivera; Víctor F. Valladolid Ocampo; Luis E. Zulueta Espíritu; Eduardo R. Espinoza Farfan; Fernando A. Sernaque Auccahuasi (Chemical Engineering Transactions, 2023)
Many countries depend on electrical energy to be able to develop their activities, and the most advisable is to generate it from renewable energy sources. Construction and demolition waste as well as WEEE (waste electrical and electronic equipment) can be used to generate electricity. Therefore, the research aimed to generate electricity from energy slabs from construction and electrical waste. For this purpose, the waste was collected, sorted and segregated, and then the slabs were made and assembled with the mechanical part. The method of transformation of mechanical to electrical energy arising from the interaction of people through the action of stepping on the slabs was used. The results obtained indicated that a single module of 14 slabs was able to charge a 12 V battery in an average of 4 hours, and by increasing the number of modules the energy collection time is substantially reduced, as long as the flow of people is increasing. Finally, it was concluded that the use of these slab modules is quite favourable for small-scale power generation, provided the necessary conditions are met.